Effect of Lavender Aromatherapy Combination and Earplug Use on Sleep Quality of Critically Patients - Kariasa, I Made; Nurhayati, Nunung; Pertiwi, Ratna (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Critically ill patients' severe symptoms and higher mortality risk can impact sleep quality. Non-pharmacological therapy, including lavender aromatherapy and earplugs, can improve sleep quality in these patients. To determine the effect of the combination of lavender aromatherapy and the use of earplugs on sleep quality in critically ill patients. Methods: This study uses a Quasy Experiment design with a one-group pretest-posttest design, involving 33 participants aged 18-65, with The Richards-Campbell Sleep Questionnaire, and uses Paired Sample t-Test for data processing. Results: In this study, an overview of the sleep quality of critical patients showed an improvement. An analysis of the sleep quality of critically ill individuals revealed a notable enhancement. The study found a significant improvement in sleep quality after the lavender aromatherapy intervention and the use of earplugs in the intervention group, as indicated by a p-value of 0.001 (p<0.05). Conclusion: The findings of this study indicate that the use of lavender aromatherapy intervention with earplugs can positively impact the sleep quality of critically ill patients. Furthermore, nurses can independently use lavender aromatherapy and earplug use as crucial nursing treatments.